2014
DOI: 10.1186/1742-4933-11-12
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of aging on the frequency, phenotype and cytokine production of human blood CD4 + CXCR5 + T follicular helper cells: comparison of aged and young subjects

Abstract: BackgroundT cell-dependent B-cell responses decline with age, indicating declined cognate helper activity of aged CD4 + T cells for B cells. However, the mechanisms remain unclear. T follicular helper (Tfh) cells, a novel T helper subset, play an essential role in helping B cells differentiation into long-lived plasma cells in germinal center (GC) or short-lived plasma cells. In the present study, we proposed that there might existe changes of proportion, phenotype or cytokine production of blood Tfh cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 49 publications
4
26
1
Order By: Relevance
“…Second, the number of patients in the various groups was not equal, and we could not control the background. Nevertheless, a study showed no significant difference between younger subjects and older subjects . In addition, the lack of patients with AIH and DILI might have affected the results of this study.…”
Section: Discussionmentioning
confidence: 70%
“…Second, the number of patients in the various groups was not equal, and we could not control the background. Nevertheless, a study showed no significant difference between younger subjects and older subjects . In addition, the lack of patients with AIH and DILI might have affected the results of this study.…”
Section: Discussionmentioning
confidence: 70%
“…The slight increase in T fh cells in blood of aged mice is likely due to memory cells, since we have shown that blood T fh and T fr cells have characteristics of memory cells (Sage et al, 2014a). Blood T fh cells in aged humans express the memory marker CD45RO (Zhou et al, 2014). T fr cells, defined as CD4 + ICOS + CXCR5 + FoxP3 + CD19 − cells, were similarly low in percentage in the iLN and blood of unimmunized young and aged mice (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found no difference in CXCR5 + cells in aged mice; however, T fr cells were not examined (Eaton et al, 2004). A recent study found slight increases in T fh cells in the blood of aged human subjects, but T fr cells were not evaluated (Zhou et al, 2014). Understanding changes in T fh and T fr cells during aging is important because both of these cell types directly interact with cognate B cells and control antibody production.…”
Section: Introductionmentioning
confidence: 99%
“…When aged B cells are exposed to self‐antigens, they can be accidentally activated and can produce low‐affinity, self‐reactive antibodies . Age‐associated increase in the circulating levels of pro‐inflammatory mediators, such as tumor necrosis factor‐α, interleukin‐6 and CRP, may recruit inflammatory cells and contribute to autoimmunity . Interferon‐α production in healthy Japanese individuals was reported to decline during mid‐50s or early 60s and then recover as they aged over 65 years, generating a concave U‐shaped pattern .…”
Section: Discussionmentioning
confidence: 99%